Why drug shortages are an ethical issue - Lipworth, Wendy (Australasian Medical Journal, 2013)
Drug shortages are a growing problem in developed countries. To some extent they are the result of technical and organisational failures, but to view drug shortages simply as technical and economic phenomena is to miss the fact that they are also ethical and political issues. This observation is important because it highlights both the moral and political imperative to respond to drug shortages as vigorously as possible, and the need for those addressing shortages to do so in ethically and politically sophisticated ways. This brief article outlines the ethical issues that need to be considered by anyone attempting to understand or address drug shortages.